The Domestic Livestock Resources of Turkey: Silkworm (Bombyx Mori, L. 1758) (Lepidoptera: Bombycidae) Lines and their Conservation - Yilmaz, Orhan; Wilson, R Trevor (International Research Journal of Insect Sciences, 2017)
This paper reviews the current status of Turkish silkworm genetic resources and activities being undertaken for their conservation. Silk production and the trade in silk have been important activities in Turkey, which lies on the ancient Silk Road, for many hundreds of years. Current production of silk is on the rise after a period of very low production. Turkey has a well-established programme of conservation and development of all of its domestic animal genetic resources, of which silkworm is considered a constituent part. Three distinct lines of native silkworm have been registered with the national standards body, the Turkish Standards Institute. Distribution of silkworm germplasm is regulated by the Ministry of Food, Agriculture and Livestock through Cooperative Unions which have more than 10,000 members. Renewed and increased international demand for natural and biological products is favourable to Turkey’s silkworm industry. The prognosis for the future development of silk production is strongly positive.